PROMOTING COMMUNICATION SKILLS AS JOB-READY SKILLS THROUGH PORTFOLIO ASSESSMENT - Yanti Nopiyanti Sopandi; Sri Setyarini; Isry Laila Syathroh (STKIP Siliwangi, 2023)
Vocational high school graduates need communication skills to be job-ready. This is a global communication tool and a job-ready skill. However, many difficulties still need in acquiring English communication skills as part of vocational high school preparation for employment, such as body language, mental issues, lack of ideas, grammatical mistakes, etc. Thus, effective teaching, learning, and evaluation may address these issues. This research examined how portfolio assessment promotes communication skills and how students react to it. Quasi-experimental research used pre-tests and post-test. However, observation and questionnaires are also employed to underpin the tests’ findings and as additional data for a more comprehensive investigation. The experimental group (30 students) and the control group (28 students) were 58 software engineering majors. Each group received three portfolio assessment-based therapy sessions. This research revealed three main findings. First, 0.000 is lower than 0.05. H0 is refused, whereas Ha is accepted. Second, the experimental group's paired sample t-test score is 14.533, substantially greater than the control group's 6.823. Third, students prioritized emotive over cognitive and behavioral factors. Keywords: communication skills, job-ready skills, portfolio assessment